COLLABORATIVE GOVERNANCE DALAM PENGEMBANGAN OBJEK WISATA BAGUS AGRO PELAGA DI DESA PELAGA KECAMATAN PETANG KABUPATEN BADUNG - I Wayan Gede Suryantika; I Wayan Sudemen; Anak Agung Gde Brahmantya Murti (Journal of Contemporary Public Administration, 2025)
Bagus Agro Pelaga is a tourism destination located in Badung Regency, particularly in the North Badung area. This destination utilizes the agricultural environment as a tourism attraction. In examining efforts to realize agro-tourism development, this study discusses the implementation of collaborative governance in the development of Bagus Agro Pelaga tourism destination in Pelaga Village, Petang District, Badung Regency. Collaborative governance is considered a new paradigm for addressing diverse issues in complex societies, with a fundamental principle emphasizing equality of relationships among stakeholders from the government, private sector, and community. This study aims to analyze the development of the Bagus Agro Pelaga tourism destination. The research employs a qualitative approach, with data collected through direct observation, interviews with relevant stakeholders including the Badung Regency Tourism Office, the management of  Bagus Agro Pelaga, and local communities and documentation studies related to the development of Bagus Agro Pelaga. The findings indicate that collaborative governance in the development of  Bagus Agro Pelaga has been implemented, but has not yet been fully optimized in all aspects. Initially originating from the agricultural sector, the area was later developed into an agro-tourism destination in response to the limited economic returns from agriculture, with the early roles of the government and local community remaining relatively limited. From an institutional perspective, there is no specific institution that functions as a mediator for collaboration among stakeholders, resulting in management that remains predominantly independent and led by the private sector. Leadership relations between the government and the management are relatively well established, as reflected in the active role of the government in regulation and training, as well as the management’s commitment to empowering the local community. The collaborative process demonstrates progress through dialogue and the creation of mutual benefits; however, it continues to face challenges related to stakeholder commitment and shared understanding. Overall, the development of  Bagus Agro Pelaga has had a positive impact on the local economy and community welfare, although stronger, more systematic, and sustainable collaborative mechanisms are still required.